INDUKSI KALUS PADA AREN (Arenga pinnata Merr.) SECARA IN VITRO MENGGUNAKAN 2,4-D - Jefri Paseno; Euis F. S. Pangemanan; Beatrix Doodoh (Universitas Sam Ratulangi, 2020)
ABSTRACT CALLUS INDUCTION ON AREN (Arenga pinnata Merr.) IN VITRO USING 2,4-D This study aims to obtain the optimal concentration of ZPT (growth regulator) 2,4-D for in vitro induction of palm callus.The research was conducted in January - May 2020 at the Laboratory of the Manado Palm Plant Research Institute.This study used MS media (Murashige and Skoog) and 5 concentrations (treatment) of 2,4-D, each treatment was repeated 5 times so that the number of experimental units was 25 bottles of culture, namely the initial concentration using 2,4-D 2 mg /l, 3 mg / l, 4 mg / l, 5 mg / l, and 6 mg / l, while for the concentration of 2,4-D after sub-culture, namely, 6 mg / l, 7 mg / l, 8 mg /l, 9 mg / l, and 10 mg / l.The results showed that the treatment of 2,4-D at a dose of 6 mg / l and 10 mg / l could induce callus on sugar palm. Keywords : Arenga pinnata Merr., Plant Tissue Isolation Method, Callus Induction, 2,4-D